(untitled) (Journal of Global Accounting, 2025)
This study examined the effect of financial management practices on performance of Ministries, Departments, and Agencies (MDAs) in South-west Nigeria. A two-stage sampling technique was used to select the participants. Primary data was obtained through the administration of questionnaire to 262 respondents out of the total population of 824, comprising employees of the Board of Internal Revenue, Accountant-General and Auditor General Office for the State, and the Ministry of Finance, Budget, and Planning across six South-west states. Data obtained was analyzed using descriptive statistics and Correlations, and Partial Least Squares-Structural Equation Model PLS-SEM. The results revealed that financial budgeting practices (t-stat=5.26, p-v<0.05) had a positive and significant effect on the performance of (MDAs) in South-West Nigeria. This suggests that effective budgeting practices enable MDAs to allocate resources more efficiently and transparently. Furthermore, financial oversight practices (t-stat=1.819 , p-v<0.10) had a positive and significant effect on organisational performance of MDAs. In addition, modern financial tools had a positive and significant effect on organisational performance of MDAs(t-stat=11.786, p-v<0.10), implies that modern financial tools allows for better cash management by consolidating government funds into a single account. The study concluded that the financial management practices serve as a critical yardstick for assessing performance within the public sector of the Southwest states. The study recommended that the government should periodically assess and update policies as well as implementation related to financial management practices. MDAs should formally adopt and institutionalize the financial management practices that have shown positive impacts on performance. Government urgently needs to reassess the internal control system so as to curb excessive spending among the MDAs